Zimowa służba żołnierzy Wojska Polskiego na Litwie i Łotwie na przełomie 1919/1920 r. - Jędrzejewska, Agnieszka (Armia kontra natura, 2020)
Winter is not the best time for miltary operations. It is necessary when political situation or international agreements are contained. In 1919 and 1920 Polish Army has served in Lithuania and Latvia in winter time. In Lithuania the soldiers have practiced patrol and garrison duty on polish-lithuanian border. In the same time other polish units have taken part in military operation in Latvia. There were the common features of these mission: winter, snow, low temperatures. In these circumstances the duty was much difficult. What else, the soldiers have fallen ill like cold and frost-bites.